Safety and immunologic effects of high- vs low-dose cholecalciferol in multiple sclerosis - Sotirchos, Elias S; Bhargava, Pavan; Eckstein, Christopher; Van Haren, Keith; Baynes, Moira; Ntranos, Achilles; Gocke, Anne; Steinman, Lawrence; Mowry, Ellen M; Calabresi, Peter A (Neurology, 2016)
To study the safety profile and characterize the immunologic effects of high- vs low-dose cholecalciferol supplementation in patients with multiple sclerosis (MS). In this double-blind, single-center randomized pilot study, 40 patients with relapsing-remitting MS were randomized to receive 10,400 IU or 800 IU cholecalciferol daily for 6 months. Assessments were performed at baseline and 3 and 6 months. Mean increase of 25-hydroxyvitamin D levels from baseline to final visit was larger in the high-dose group (34.9 ng/mL; 95% confidence interval [CI] 25.0-44.7 ng/mL) than in the low-dose group (6.9 ng/mL; 95% CI 1.0-13.7 ng/mL). Adverse events were minor and did not differ between the 2 groups. Two relapses occurred, one in each treatment arm. In the high-dose group, we found a reduction in the proportion of interleukin-17(+)CD4(+) T cells (p = 0.016), CD161(+)CD4(+) T cells (p = 0.03), and effector memory CD4(+) T cells (p = 0.021) with a concomitant increase in the proportion of central memory CD4(+) T cells (p = 0.018) and naive CD4(+) T cells (p = 0.04). These effects were not observed in the low-dose group. Cholecalciferol supplementation with 10,400 IU daily is safe and tolerable in patients with MS and exhibits in vivo pleiotropic immunomodulatory effects in MS, which include reduction of interleukin-17 production by CD4(+) T cells and decreased proportion of effector memory CD4(+) T cells with concomitant increase in central memory CD4(+) T cells and naive CD4(+) T cells. This study provides Class I evidence that cholecalciferol supplementation with 10,400 IU daily is safe and well-tolerated in patients with MS and exhibits in vivo pleiotropic immunomodulatory effects.